2008
DOI: 10.1038/ajh.2008.184
|View full text |Cite
|
Sign up to set email alerts
|

Risk for Obstructive Sleep Apnea by Berlin Questionnaire, But Not Daytime Sleepiness, Is Associated With Resistant Hypertension: A Case-control Study

Abstract: High risk for OSAS assessed by the Berlin Questionnaire is highly prevalent and associated with resistant hypertension. This questionnaire may be used as screening for OSAS in patients with this clinical condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
48
0
9

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(63 citation statements)
references
References 23 publications
5
48
0
9
Order By: Relevance
“…The BQ includes questions on obesity, hypertension, snoring, daytime sleepiness and fatigue 17 . We demonstrated that a positive response to the questionnaire was independently associated with resistant hypertension 18 .…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…The BQ includes questions on obesity, hypertension, snoring, daytime sleepiness and fatigue 17 . We demonstrated that a positive response to the questionnaire was independently associated with resistant hypertension 18 .…”
mentioning
confidence: 75%
“…Patients with OSA had a greater recurrence rate of atrial fibrillation after catheter arrhythmia ablation than patients without OSA. The prevalence of a high risk factor of coronary artery disease associated with OSA identified by the BQ was 80% in patients with resistant hypertension versus 44% in patients with controlled hypertension 18 . Drager et al 42 found similar performance of the BQ in the hypertensive population.…”
Section: Controls Casesmentioning
confidence: 93%
“…The Berlin Questionnaire (BQ), one of the most widely used screening tools, has been validated as a predictor of OSA in the primary care setting 24 and is now commonly used to assess need for PSG. [24][25][26][27][28] It has, however, not performed as well in the general surgery population, 23,27 and its utility in the bariatric surgery population is unproven. Given that "obesity" is an indicator of increased OSA risk per the BQ scoring scheme, the discriminatory ability of the BQ may be worse among bariatric surgery patients, all of whom are obese.…”
Section: Assessment Of Obstructive Sleep Apnea In Adults Undergoingmentioning
confidence: 99%
“…Despite these limitations, our results indicate the major importance of the complex evaluation of nearly 20 ambulatory BP variables selected by comparison with cardiorespiratory indices obtained during parallel PSG examination. Recent results have indicated that an increased risk for SAHS is highly prevalent when assessed by a special Berlin questionnaire, and it is frequently associated with resistant hypertension [38]. ABPM should be evaluated in patients with hypertension to assess and prevent risk of morbidity and mortality [39].…”
Section: 1mentioning
confidence: 99%